Hazardous birthday drinking among young people: population‐based impacts on emergency department and in‐patient hospital admissions. (22nd July 2014) - Callaghan, Russell C.; Sanches, Marcos; Gatley, Jodi M.; Liu, Lon‐Mu; Cunningham, James K.
Abstract Background and Aims There is growing concern about the possible adverse health impacts of binge drinking during birthday celebrations among adolescents and young adults. We estimate the impacts of birthday alcohol use on adolescent and young adult in‐patient/emergency department (ED) hospital admissions. Design We employed Autoregressive Integrated Moving Average (ARIMA) intervention analysis to assess whether the rate of ICD‐10 alcohol‐use‐disorder (AUD) events per 1000 in‐patient/ED admissions increased significantly during birthday weeks. Setting All in‐patient/ED admissions in Ontario, Canada from 1 April 2002 to 31 March 2007. Participants Individuals aged 12–30 years. Measurements AUD events per 1000 in‐patient/ED admissions by age in weeks. Findings Multiple increases were found. The largest occurred during the birthday week of 19 years of age, the beginning of the minimum legal drinking age (MLDA) in Ontario: AUD admission rates increased (spiked) by 38.30 per 1000 total admissions [95% confidence interval (CI) = 34.66–41.94] among males (a 114.3% increase over baseline), and by 28.13 (95% CI = 25.56–30.70) among females (a 164.0% increase). Among both genders, the second largest birthday‐week spikes occurred during ages 20–22 years, followed by somewhat lower but still pronounced birthday‐week spikes during ages 23–26 years and 30 years (all these spikes: P < 0.05). Birthday‐week spikes occurred as early as age 16 years for males and 14 years for females (both spikes: P < 0.05). Conclusions There appears to be an increase in alcohol‐related adverse events from drinking around the time of one's birthday among young adults in Canada.